Determination of fertilization rates and mulching to improve growth of RRIM 3001 rubber clone in non-traditional rubber areas - Razman, Muhammad Zahidin (2015)
The hectarage of rubber has decreased year by year. Thus, future planting has been pushed to the problem soils which are class III, IV and V soils. The objectives of this study are to evaluate the growth and physiological traits of RRIM3001 planted in non-traditional area which is Gajah Mati and Jabil series, to measure the optimum rate of fertilizer of RRIM3001 planted in these soils and to evaluate the effect of mulching practices as soil amelioration in Batang Merbau series on soil nutrient content and growth of RRIM 3001. In experiment 1, the study was conducted at Kampung Chin Chin and Kampung Kelubi, Jasin, Melaka. This study consists of high productive rubber clone, RRIM3001 also known as "Klon 1 Malaysia" treated with four levels of fertilizer rates at three months intervals for a period of one year. The fertilizer rates were divided into four levels, Tl (0 g/tree per year), T2 (480 g/tree per year), T3 (720 g/tree per year) and T4 (960 gl+xee per year). The fertilizer used in this study is NPK Yellow (15: 15:6:4). The second experiment was implemented at Ladang Komoditi, Jasin, This study also consists of RRIM 3001 treated with five levels of fertilizer rates, Tl (0 g/tree per year), T2 (480 gf txee per year), T3 (720 g/tree per year), T4 (480 g/tree per year plus mulching) and T5 (720 g/tree per year plus mulching) by applying the NPK Yellow fertilizer (15: 15:6:4) at three months intervals for a period of one year. One type of mulching system had been practiced namely Ecomat, processed oil palm fibre material (Ecofibre Bhd Malaysia) and the size of ecomat is 1.0 m x 1.0 m x 9mm. The experimental set up was a random completely block design (RCBD) with three replications. The study duration was one year period. In experiment 1, the result obtained showed there were significant interactions between depth and fertilizer treatment in both of type of soil series, Gajah Mati and Jabil series. In terms of the total plant height and girth increment, there were significant difference between Gajah Mati and Jabil series where Gajah Mati showed better performance compared to Jabil series. This is attributed to the drainage status of the soil which is Gajah Mati is well drained whereas Jabil is poorly drained. From the result in experiment 2, it showed there were significant interactions between depth and fertilizer treatment in Batang Merbau series. The fertilizer treatment of T5 showed the best performance in term of height and girth conditions compared to the other treatments. As conclusion, the data of growth of RRIM 3001 planted on Gajah Mati and Jabil series showed that applying adequate rate of fertilizer is dependent on the type of soil. It indicates that the current rate of fertilizer that was recommended is inadequate and hence extra dosage of fertilizer maybe necessary. In terms of plant girth, it was shown that applying fertilizer up to the rate of 658 g/tree per year responded to quadratic model with the maximum of 10.3 cm/year on Gajah Mati compared to Jabil, 715 g/tree per year which gave the maximum girth of 8.4 cm/year. In this study, it indicates that the recommended rate of fertilizer is inadequate and hence extra dosage of fertilizer maybe necessary. The effect of mulching practices give favourable effect on the growth of RRIM 3001 based on girth, soil nutrient and cholorophyll content. This study shows the deficiency of Potassium (K) in foliar analysis. The new formulation of fertilizer especially the ratio of Potassium should be increased on non-traditional area specifically. From this study, it can be recommended that for non-traditional area especially on Jabil, Gajah Mati and Batang Merbau series, fertilizer use should contain higher Kcompared to the NPKYellow (15:15:6:4).